Transient elevation of serum 5-HIAA by dietary serotonin and distribution of 5-HIAA in serum protein fractions. (July 2015) - Tohmola, Niina; Johansson, Anna; Sane, Timo; Renkonen, Risto; Hämäläinen, Esa; Itkonen, Outi
Introduction: Dietary serotonin increases urinary secretion of 5-HIAA. A falsely elevated 5-HIAA may lead to incorrect suspicion of a neuroendocrine tumour. Therefore, we determined the effect and duration of dietary serotonin on serum 5-HIAA concentration. We also studied the distribution of 5-HIAA in serum fractions. Methods: We used serum samples from healthy volunteers (31 women and four men). All test subjects avoided serotonin-containing foods for three days before sample collection. They then ate either pineapple, banana, kiwi fruit, tomato or walnuts and additional blood samples were taken after 2, 4, 6, 24, 48 and 72 h. To study the distribution of 5-HIAA in serum, samples from a healthy individual, a test person who had ingested walnuts, and from a neuroendocrine tumour patient were fractionated by gel filtration chromatography. The fractions were analysed for 5-HIAA. Results: Serum 5-HIAA concentration increased significantly ( P ≤ 0.001) within 2 h after ingestion of serotonin-containing food. After 2 h, 5-HIAA concentration started to decrease and reached the baseline concentration within 24 h. A calculated half-life of 5-HIAA in circulation was 1.3 h. In fractionated serum, 5-HIAA was found not only in free form but also in the albumin and α2-globulin fractions. Conclusions: The increase of serum 5-HIAA caused by dietary serotonin is significant but transient. Therefore, serotonin-containing foods should be avoided for one day before blood sampling. In serum, 5-HIAA is free and apparently bound to albumin. Minor amounts were also found in the α2-globulin fraction. Our liquid chromatography tandem mass spectrometry assay measures free 5-HIAA in serum.